Targeting prostate cancer with compounds possessing dual activity as androgen receptor antagonists and HDAC6 inhibitors. Issue 21 (1st November 2016) - Jadhavar, Pradeep S.; Ramachandran, Sreekanth A.; Riquelme, Eduardo; Gupta, Ashu; Quinn, Kevin P.; Shivakumar, Devleena; Ray, Soumya; Zende, Dnyaneshwar; Nayak, Anjan K.; Miglani, Sandeep K.; Sathe, Balaji D.; Raja, Mohd.; et al.
Graphical abstract: Abstract: While enzalutamide and abiraterone are approved for treatment of metastatic castration-resistant prostate cancer (mCRPC), approximately 20–40% of patients have no response to these agents. It has been stipulated that the lack of response and the development of secondary resistance to these drugs may be due to the presence of AR splice variants. HDAC6 has a role in regulating the androgen receptor (AR) by modulating heat shock protein 90 (Hsp90) acetylation, which controls the nuclear localization and activation of the AR in androgen-dependent and independent scenarios. With dual-acting AR–HDAC6 inhibitors it should be possible to target patients who don't respond to enzalutamide. Herein, we describe the design, synthesis and biological evaluation of dual-acting compounds which target AR and are also specific towards HDAC6. Our efforts led to compound10 which was found to have potent dual activity (HDAC6 IC50  = 0.0356 μM and AR binding IC50  = <0.03 μM). Compound10 was further evaluated for antagonist and other cell-based activities, in vitro stability and pharmacokinetics.